2008
DOI: 10.1017/s0022112008000815
|View full text |Cite
|
Sign up to set email alerts
|

Shock tube flows past partially opened diaphragms

Abstract: Unsteady compressible flows resulting from the incomplete burst of the shock tube diaphragm are investigated both experimentally and numerically for different initial pressure ratios and opening diameters. The intensity of the shock wave is found to be lower than that corresponding to a complete opening. A heuristic relation is proposed to compute the shock strength as a function of the relative area of the open portion of the diaphragm. Strong pressure oscillations past the shock front are also observed. Thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 17 publications
1
25
0
Order By: Relevance
“…It should be noted here that it takes a distance of 10-20 tube diameters downstream from the diaphragm before a well-formed shock wave is evident. It is, therefore, surprising that in the numerical study presented in [12] a shock is seen diffracted over the open diaphragm (see Fig. 4 in [12]).…”
Section: Diaphragm Opening Previous Investigationsmentioning
confidence: 90%
See 2 more Smart Citations
“…It should be noted here that it takes a distance of 10-20 tube diameters downstream from the diaphragm before a well-formed shock wave is evident. It is, therefore, surprising that in the numerical study presented in [12] a shock is seen diffracted over the open diaphragm (see Fig. 4 in [12]).…”
Section: Diaphragm Opening Previous Investigationsmentioning
confidence: 90%
“…Recently Gaetani et al [12] conducted an experimental and numerical study regarding the effect of incomplete burst of the shock tube diaphragm on the resulting flow. They offered a heuristic relation for estimating the resulting shock wave strength as a function of the relative area of the open portion of the diaphragm.…”
Section: Diaphragm Opening Previous Investigationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The net result of this process is the weakening of shock intensity and an increase in shock formation distance. Houas et al [23] studied the effect of the ratio between ruptured area and shock tube area and found similar results to Gaetani et al [13]. They found that as this area ratio decreased, the shock formation distance increased, whilst the pressure ratio across the shock decreased.…”
Section: Motivation For Current Studymentioning
confidence: 69%
“…Gaetani et al [13] employed experimental and numerical techniques to investigate the resulting flow field from incomplete diaphragm rupture. A complex flow field was described where the leading shock diffracted around the diaphragm orifice.…”
Section: Motivation For Current Studymentioning
confidence: 99%